Recruitment, enrollment & data collection with victims of elder abuse and neglect identified from police incident reports. Issue 5 (20th October 2018) - Pickering, Carolyn E. Z.; Maxwell, Christopher
ABSTRACT: This study evaluated the success of researcher-generated recruitment, enrollment, data collection, and safety protocols for field research with victims of elder abuse and neglect (EAN) identified from police incident reports in terms of their success including cost-effectiveness, ability to generate a representative sample, and safety. After reviewing 492 police incident reports involving victims age 65 years or older to identify cases of EAN 62 victims were identified. Mail, phone, and in-person recruitment strategies were used. After 259 recruitment attempts, 52 (84%) eligible victims were contacted, of which 24 (46%) consented to participate. Phone calls were the least expensive mechanism to produce a successfully enrolled participant. Findings from a regression show completion of a research interview could not be predicted by victim, suspect, or offense characteristics, indicating that the recruited victims likely represent the population they were drawn from. No safety or adverse events occurred.